γ-ray assisted synthesis of silver nanoparticles in chitosan solution and the antibacterial properties - Huang, Nay Ming; Radiman, Shahidan; Lim, Hong Ngee; Khiew, Poi Sim; Chiu, Wee Siong; Lee, K. H.; Ahmad, Syahida; Hashim, Rauzah; Chia, Chin Hua (Elsevier, 2009)
In the present study, chitosan had been utilized as a “green” stabilizing agent for the synthesis of spherical silver nanoparticles in the range of 5–30 nm depending on the percentage of chitosan used (0.1, 0.5, 1.0 and 2.0 wt%) under γ-irradiation. X-ray diffractometer identified the nanoparticles as pure silver having face-centered cubic phase. Ultraviolet–visible spectra exhibited the influence of γ-irradiation total absorbed dose and chitosan concentration on the yield of silver nanoparticles. The antibacterial properties of the silver nanoparticles were tested against Methicillin-resistant Staphylococcus aureus (MRSA) (gram-positive) and Aeromonas hydrophila (gram-negative) bacteria. This work provides a simple and “green” method for the synthesis of highly stable silver nanoparticles in aqueous solution with good antibacterial property.